2001
DOI: 10.1046/j.1468-1331.2001.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Musicogenic epilepsy with ictal single photon emission computed tomography (SPECT): could these cases contribute to our knowledge of music processing?

Abstract: Musicogenic epilepsy has a strong correlation with the temporal lobe with a right-sided preponderance. We report the case of a 48-year-old woman whose seizures began at the age of 32 years. Her prenatal, natal and childhood histories were unremarkable and her family history was negative for epilepsy. She had typical complex partial seizures with chewing automatisms. Cranial computed tomography, magnetic resonance imaging (MRI) and interictal SPECT showed no abnormality. Interictal EEG showed paroxysmal bitempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 8 publications
(12 reference statements)
2
30
0
4
Order By: Relevance
“…This ERP result was interpreted as a facilitated attention allocation and memory updating processes when hearing music of a familiar style. In a musicogenic epilepsy case study, Genc et al (2001) showed that only Turkish music was able to trigger seizures in this 48-year-old Turkish female but not other musical styles, e.g., Western music. Those two studies suggest distinct neural substrates engaged in the processing of culturally familiar music in comparison to unfamiliar music.…”
Section: Introductionmentioning
confidence: 77%
“…This ERP result was interpreted as a facilitated attention allocation and memory updating processes when hearing music of a familiar style. In a musicogenic epilepsy case study, Genc et al (2001) showed that only Turkish music was able to trigger seizures in this 48-year-old Turkish female but not other musical styles, e.g., Western music. Those two studies suggest distinct neural substrates engaged in the processing of culturally familiar music in comparison to unfamiliar music.…”
Section: Introductionmentioning
confidence: 77%
“…These patients may experience unprovoked seizures as well, whereas others have exclusively music-induced seizures [41,42].…”
Section: Musicogenic Epilepsymentioning
confidence: 99%
“…Commonly, the inciting music is reported to induce a specific emotion in the affected listener, such as melancholy or sentimentality, whereas others may not be aware of a specific emotional trigger [42]. In some cases, seizures may initially occur exclusively in response to music and subsequently generalize to other auditory stimuli, such as spoken voice or nonmusical sounds [41,45].…”
Section: Musicogenic Epilepsymentioning
confidence: 99%
“…Thus researchers concluded that hearing music of a culturally familiar style increased the allocation of attention resources during memory updating processes [1] . And a musicogenic epilepsy case showed only Turkish music triggered seizures in Turkish subjects but not other musical styles [10] .…”
Section: Introductionmentioning
confidence: 99%